Sharia Financial Literacy in the Digital Era: The Role of the Younger Generation in Embracing the Transformation of Islamic Finance - Hayati, Fauzia Kamila; Pertiwi, Ruspita Rani (Universitas Muhammadiyah Surakarta, 2025)
The level of Islamic financial literacy among the younger generation remains relatively low, while digital transformation in the financial sector is developing rapidly. This situation then creates a gap between the ability to utilise technology and an adequate understanding of Islamic financial concepts. This study aims to systematically review the academic literature on Islamic financial literacy among the younger generation in the digital era, identifying opportunities, challenges, and strategies for improving literacy. The method used was a Systematic Literature Review (SLR) of 20 scientific articles published between 2018 and 2025, focusing on three main aspects: literacy level, utilization of digitalization, and challenges in disseminating Islamic financial education. The study results indicate that digitalization has significant potential to increase access and effectiveness of Islamic financial education through social media platforms, financial applications, and digital banking services. However, most educational content remains descriptive, lacks interactivity, and is not fully aligned with the characteristics of the younger generation. Therefore, a collaborative strategy is needed between Islamic financial institutions, educational institutions, and other stakeholders to develop engaging, applicable, and sustainable Islamic financial literacy content. This research offers important implications for developing a more innovative and relevant Islamic financial education model tailored to the needs of the younger generation in the digital era.